Comparative analysis among molecular targets for detection of Helicobacter pylori - Pedro Eduardo Almeida Silva; Thaísa Bozzetti Gautério; Ivy Bastos Ramis; Júlia Vianna; Andrea Von Groll (Universidade de Santa Cruz do Sul, 2015)
KEYWORDS: Helicobacter pylori. Polymerase Chain Reaction. Molecular Diagnostic Techniques